2008
DOI: 10.1097/wnp.0b013e31816ef739
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Suppression of Postexercise Facilitation of Motor Evoked Potentials During Alternate Phases of Bipolar Disorder

Abstract: The current study sought to longitudinally evaluate the postexercise facilitation of motor evoked potentials (MEP) in two patients during different phases of short-circle depressive-manic disorder. Each study included 50 baseline MEP elicited by transcranial magnetic stimulation, followed by 50 MEP immediately after nonfatiguing exercise of the examined muscle. Postexercise MEP facilitation, expressed as percentage of baseline value, varied from 71% to 119% and from 99% to 107% in each patient, respectively, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Studies using transcranial magnetic stimulation paradigms showed a significant deficit in cortical inhibition in BD patients compared to healthy controls (Levinson et al, 2007 ; Chroni et al, 2008 ), which is in agreement with the data showing increased glutamatergic neurotransmission in BD patients. The hippocampus, another brain region affected in BD, also is the site of adult neurogenesis (Vadodaria and Gage, 2014 ).…”
Section: Glutamatergic Neurotransmission and Hyperexcitabilitysupporting
confidence: 83%
“…Studies using transcranial magnetic stimulation paradigms showed a significant deficit in cortical inhibition in BD patients compared to healthy controls (Levinson et al, 2007 ; Chroni et al, 2008 ), which is in agreement with the data showing increased glutamatergic neurotransmission in BD patients. The hippocampus, another brain region affected in BD, also is the site of adult neurogenesis (Vadodaria and Gage, 2014 ).…”
Section: Glutamatergic Neurotransmission and Hyperexcitabilitysupporting
confidence: 83%
“…The articles reviewed here provide neurophysiological evidence for altered cortical excitability (Maeda et al., 2000; Fitzgerald et al., 2004; Levinson et al., 2010; Spampinato et al., 2013; Concerto et al., 2013; Croarkin et al., 2013; Veronezi et al., 2016) and synaptic plasticity (Chroni et al., 2008; Bajwa et al., 2008; Spampinato et al., 2013; Croarkin et al., 2013; Player et al., 2013; Kuhn et al., 2016) in MDD. These data confirm the findings of previous investigations that have used different approaches (Debener et al., 2000; Normann et al., 2007; Teyler and Cavus, 2007; Salustri et al., 2007; Nissen et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a number of studies have shown that there is a significant decrease in postexercise facilitation in these individuals (Samii et al., 1996; Shajahan et al., 1999a, 1999b; Reid et al., 2002; Chroni et al., 2008) that is probably linked to an imbalance between inhibitory and excitatory inputs at the level of cortical-spinal neurons. This observation, which has also been reported in schizophrenia (Reid et al., 2002; Chroni et al., 2002), might explain the symptoms reported by these patients, which can include fatigue, weakness, motor inertia, and apathy, and indicates the existence of a potentially strong relationship between psychiatric disorders and motor output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cortical inhibition processes are under the control of GABAergic interneurons, these results show GABAergic pathway involvement in depressive pathologies. The one longitudinal study in bipolar patients was led by Chroni et al (2008). The authors evaluated the post-exercise facilitation of MEP in two patients during different phases of rapid cycling depressive-manic disorder.…”
Section: Introductionmentioning
confidence: 99%